2011
DOI: 10.1093/nar/gkr1176
|View full text |Cite
|
Sign up to set email alerts
|

2A peptides provide distinct solutions to driving stop-carry on translational recoding

Abstract: Expression of viral proteins frequently includes non-canonical decoding events (‘recoding’) during translation. ‘2A’ oligopeptides drive one such event, termed ‘stop-carry on’ recoding. Nascent 2A peptides interact with the ribosomal exit tunnel to dictate an unusual stop codon-independent termination of translation at the final Pro codon of 2A. Subsequently, translation ‘reinitiates’ on the same codon, two individual proteins being generated from one open reading frame. Many 2A peptides have been identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 28 publications
8
121
0
Order By: Relevance
“…This 'self-cleavage' peptide composed of 2A and 2B, both of which are translated from one mRNA molecule and function independently (42). Therefore, the 2A peptide is well used for the multiple expression of foreign proteins (43,44). In the present study, we confirmed that the adenovirus encoding both FOXL1 and PP2A with the '2A peptide' linker overexpressed both tumor suppressors in pancreatic cancer cells, and exerted synergistic growth inhibition of pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 77%
“…This 'self-cleavage' peptide composed of 2A and 2B, both of which are translated from one mRNA molecule and function independently (42). Therefore, the 2A peptide is well used for the multiple expression of foreign proteins (43,44). In the present study, we confirmed that the adenovirus encoding both FOXL1 and PP2A with the '2A peptide' linker overexpressed both tumor suppressors in pancreatic cancer cells, and exerted synergistic growth inhibition of pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 77%
“…34,39,40 2A peptides with higher cleavage efficiency could also be identified by screening other 2A peptides, which were recently identified, but have yet to be well characterized. 26 The consensus sequence for furin cleavage is RXXR, but the potential for actual cleavage is dependent on the amino acids immediately surrounding the recognition site. 44 A recent study found that the 2 amino acids upstream and 4 amino acids downstream of RXXR were critical for cleavage and the frequency of these amino acids in the best substrates for furin cleavage were determined.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Many 2A peptides have been identified from viruses. 26 F2A from the foot-andmouth disease virus, which is the most studied 2A, has been used for mAb expression in mammalian cells and for in vivo gene therapy. 18,21,[27][28][29][30][31] 2A peptides have approximately 20 amino acids and "self-cleavage" occurs between the last 2 amino acids, glycine (G) and proline (P).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although StopGo does not function Avoidance of reporter assay distortions www.rnajournal.org 1287 in bacteria (Donnelly et al 1997), it does function in all eukaryotic systems tested so far including in yeast (Doronina et al 2008;Sharma et al 2012), insects (Diao and White 2012), and plants (Sun et al 2012), indicating that the pSGDluc system can be easily adapted for other organisms.…”
Section: Variants For Specialized Usage and Caveatsmentioning
confidence: 99%